Pola Sebaran dan Keanekaragaman Jenis Lamun di Perairan Tanjung Pallette dan Tangkulara, Kabupaten Bone, Provinsi Sulawesi Selatan - Katarina Hesty Rombe; Dwi Rosalina; Khairul Jamil; Agus Surachmat; Ali Imran (Jurnal Airaha, 2020)
The aims of this study was to determine the distribution patterns and diversity of seagrass in Pallette and Tangkulara waters. This research was conducted for two months, from August to September 2019. Data collection was carried out at two points with three replications each. Seagrass data retrieval uses the line and quadrant transect method. The results showed that there were 5 species of seagrass found in the Pallette and Tangkulara Waters, namely Enhalus acoroides, Thalassia hemprichii, Halodule uninervis, Cymodocea rotundata, and Halophila sp. The diversity of seagrass species in the Pallette and Tangkulara Waters was in the low category. Distribution patterns of all species of seagrass Thalassia hemprichii Halodule uninervis, Cymodocea rotundata, Halophila sp. has a grouped distribution pattern value while for Enhalus acoroides the distribution pattern is equal.